POLITISASI BIROKRASI: Analisis Dampak Inkonsistensi Interpretasi Makna Pasal Dalam Undang-Undang Aparatur Sipil Negara - Hidayat, Fauzan (Fakultas Politik Pemerintahan, 2021)
The politicization of the bureaucracy is a polemic that has become a parasite in the administration of government which has not yet been completely resolved. This has a very bad impact on the integrity of ASN and the quality of public services provided to the community. The attitude of political officials who take advantage of bureaucrats for their personal and group interests greatly injures the professionalism of government administrators in the technical field. This problem arises because of the bias in the meaning of the provisions of Article 1 Paragraph (14) of Law Number 5 of 2015 concerning State Civil Apparatus that the Civil Service Supervisory Officer (PPK) is an official who has the authority to determine the appointment, transfer, and dismissal of ASN employees and development of ASN management in government agencies. For this reason, it is necessary to (1) identify the problems of politicization of the bureaucracy in determining the appointment, transfer, and dismissal of ASN employees by regional heads; and (2) Analysis of the best policy alternatives to overcome these problems. The author uses a qualitative descriptive method because it examines the pattern of the relationship between politics and bureaucracy with the theory of Interdependence between policy, politics and administration and the concept of the dichotomy of political officials and bureaucratic officials then analyzes the impact of ASN regulations through the Regulatory Impact Analysis (RIA) method.